Waste management and disease spread potential: A case study of SARS-CoV-2 in garbage dumping sites in Bangkok and its vicinity - Anuwat Wiratsudakul; Ladawan Sariya; Weena Paungpin; Sarin Suwanpakdee; Tatiyanuch Chamsai; Siriporn Tangsudjai; Benjaporn Bhusri; Peerawat Wongluechai; Kanittha Tonchiangsai; Walasinee Sakcamduang; Witthawat Wiriyarat; Nareerat Sangkachai (One Health)
During the coronavirus disease 2019 (COVID-19) pandemic, hospitals and households have used personal protective equipment (PPE), such as masks and gloves. Some of these potentially infectious materials were discarded with other household wastes in garbage dumping sites. Thus, this study aimed to detect the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in contaminated wastes, environments, and mammals scavenging around these sites. From September to October 2022, we visited three garbage dumping sites located in Bangkok, Nakhon Pathom, and Nonthaburi provinces of Thailand. Oral, nasal, rectal swabs, and blood samples were collected from small mammals, stray dogs, and cats. Masks, gloves, soil, and water samples from the sites were additionally collected. Of the 582 samples collected from 238 animals, none tested positive for SARS-CoV-2 in the virus isolation, real-time reverse-transcription polymerase chain reaction, and neutralizing antibody detection. However, one sample (1.18 %; 1/85) from a rat (Rattus spp.) captured in Nonthaburi was serologically positive in the indirect enzyme-linked immunosorbent assay. The surveillance of coronaviruses in rats is strongly encouraged because rats may harbor different zoonotic pathogens, including unknown potentially zoonotic coronaviruses. Moreover, two face mask samples (4.65 %; 2/43) collected from the dumping site in Nakhon Pathom tested positive for SARS-CoV-2 by real-time RT-PCR. To reduce environmental contamination, detecting the SARS-CoV-2 viral genome in contaminated face masks highlights the critical need for proper waste management in households and communities in Thailand. Thus, to minimize exposure and prevent onward transmission, waste management personnel, including garbage dump staff and waste pickers, should be equipped with appropriate PPE and receive regular training on safe handling and disposal.